« Extraterrestres ou spéculatives » - Aurore Turbiau (Glad!)
This article is an exploration, problematized from the perspective of the notion of “constellation”, of the book QuebeQueer: Le queer dans les productions littéraires, artistiques et médiatiques québécoises, published in 2020 by the Presses de l’Université de Montréal, edited by Isabelle Boisclair, Guillaume Poirier Girard and Pierre-Luc Landry. It reviews the various positions and definitions of the notion of “queer” that are proposed in this dense work, which is mainly centred on a literary questioning. It points out the bibliographical references that currently appear to be crucial for thinking about queer, and tackles a certain number of related notions and questions - representation, affect, stylization of identities, relations between activism and literature, subjectivities, spaces and temporalities, etc. The second part of the article focuses more specifically on proposing a cross-problematization of queer and the notion of constellations, sketching out some hypotheses based on the articles proposed in QuébeQueer: queer, like constellations, are notions that make it possible to « reappropriate, recode, and redeploy » the meaning of creations and the links they establish with each other.